Presencia del cacao en la historia manabita y su comodificación para el agroturismo de la zona centro de Manabí - García Tamayo, Japsson Vicente (2024)
The objective is to determine sustainable tourism management strategies based on cultural practices around cocoa in the central area of Manabí, for this the research methodology includes inductive, descriptive and bibliographic and documentary review methods, for which survey techniques were applied to 198 owners of cocoa-producing farms and 4 interviews with community leaders, association leaders and diagnostic survey through the FODA matrix with 16 producers in the sector. The research configured a methodological process in 3 phases: the first aimed at characterizing the cultural practices associated with cocoa production, the second phase allowed for the analysis of the economic impact generated by the presence of cocoa in the study area, and the third phase corresponding to the promotion of a management model that allows the strategic commodification of the agrotourism activity to be made viable, describing four strategic components such as the design of agrotourism activities, training in issues related to tourism in rural areas, the implementation of complementary services and promotion of tourist demand. The results indicate that the historical factors, the cultural and traditional practices of the production of Fine Aroma Cocoa are generated from the generational and family handover, which has fostered the development of the rural economy, so that the implementation of operational actions makes possible the agrotourism comodification of cocoa, allowing the consolidation of local identity and natural heritage in the territory.